Role of central vagal 5-HT3 receptors in gastrointestinal physiology and pathophysiology - Browning, Kirsteen N. (Frontiers in Neuroscience, 2015)
Vagal neurocircuits are vitally important in the co-ordination and modulation of GI reflexes and homeostatic functions. 5-hydroxytryptamine (5-HT; serotonin) is critically important in the regulation of several of these autonomic gastrointestinal (GI) functions including motility, secretion and visceral sensitivity. While several 5-HT receptors are involved in these physiological responses, the ligand-gated 5-HT3 receptor appears intimately involved in gut-brain signaling, particularly via the afferent (sensory) vagus nerve. 5-HT is released from enterochromaffin cells in response to mechanical or chemical stimulation of the GI tract which leads to activation of 5-HT3 receptors on the terminals of vagal afferents. 5-HT3 receptors are also present on the soma of vagal afferent neurons, including GI vagal afferent neurons, where they can be activated by circulating 5-HT. The central terminals of vagal afferents also exhibit 5-HT3 receptors that function to increase glutamatergic synaptic transmission to second order neurons of the nucleus tractus solitarius within the brainstem. While activation of central brainstem 5-HT3 receptors modulates visceral functions, it is still unclear whether central vagal neurons, i.e., nucleus of the tractus solitarius (NTS) and dorsal motor nucleus of the vagus (DMV) neurons themselves also display functional 5-HT3 receptors. Thus, activation of 5-HT3 receptors may modulate the excitability and activity of gastrointestinal vagal afferents at multiple sites and may be involved in several physiological and pathophysiological conditions, including distention- and chemical-evoked vagal reflexes, nausea, and vomiting, as well as visceral hypersensitivity.